PENDUGAAN KERENTANAN EROSI DAN SEDIMENTASI DAS MENTAYA MENGGUNAKAN PERSAMAAN RUSLE - Silvia, Novi; Setiawan, Akemat Rio; Wiwoho, Bagus Setiabudi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Erosion and sedimentation are two significant issues influenced by hydrodynamic activities and sediment transport, leading to many hydrological changes in a watershed. Erosion in a watershed streamflow will cause sedimentation and riverbed shallowing. A similar situation occurs in the Mentaya Watershed, where sedimentation has triggered a rise in river water levels, increasing the potential for flooding during rainfall events. The RUSLE method in assessing erosion rates provides results that can inform effective erosion control strategies under the current conditions of the Mentaya Watershed. This study aimed to identify the current conditions of the Mentaya Watershed and monitor the estimated magnitude of erosion and sedimentation through RUSLE calculations using Google Earth Engine (GEE). The study results showed a dynamic increase in erosion rates in the Mentaya Watershed from 2016 to 2024, with the highest predicted figure reaching 509.84 tons/ha/year in 2024. The highest amount of transported sediment was found in 2024, occurring in areas with slopes greater than 40%, while the lowest transported sediment was found in areas with moderate slopes of 10-20%. The sedimentation level in the Mentaya Watershed was expected to continue increasing in line with the high erosion rates. This condition will significantly affect the levels of erosion and sedimentation vulnerability in the Mentaya Watershed.